Altered reality [videorecording (DVD)] - Agron, Charles; Henriksen, Lance, 1940-; Bell, Tobin; Asner, Edward (Vision Films, 2025)
While a man is at his family vacation home, he is given a mysterious yet-to-be discovered miracle drug worth billions. As he oversees his new business, he neglects his family and his young daughter unexpectedly disappears, shattering his life. He learns that the vacation spot is actually a nexus of energy that allows time travel, offering him the chance to save his daughter and family.